Seasonal dynamics of zooplankton in lakes of different trophic status - Selivonchyk, Iryna N. (Experimental Biology and Biotechnology, 2021)
In the article, we present the data about the dominant complexes of zooplankton species in the pelagic zone of lakes Naroch, Myastro, Batorino (2014 –2019), Malye and Bolshie Shvakshty (2014 –2015), Svir (2018). The seasonal dynamics of zooplankton is analysed. The contribution of taxonomic groups and individual species in the abundance and biomass of zooplankton in lakes with different trophic status is studied. We noted two peaks in the seasonal dynamics of zooplankton. Rotifers prevailed in the spring, while Crustacea dominated in the summer-autumn period. The relative biomass of cladocerans increased and the proportion of copepods decreased with the increasing of trophic status of the lakes.